METODE PEMBINAAN AKHLAK DALAM PENINGKATAN PENGAMALAN IBADAH PESERTA DIDIK DI SMP N 4 SEKAMPUNG LAMPUNG TIMUR - Bayu Prafitri (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
Islamic religious education teachers are people who provide knowledge with the aim of educating and fostering the morality of students as good people. In the process of moral development of students, an Islamic education teacher in delivering material must have the right method. Moral material is one of the most dominating material in the formation of personality of students. If the provision of this material is maximally endeavored by the religious teacher, the morality of the participants should be ascertained to be better. In this case the Islamic religious education teacher plays the first and foremost role in the process of moral development of his students. For the success of the moral development process, an Islamic religious education teacher must be able to use several methods in building it to improve the worship experience.Departing from that background, the author wants to discuss it in a thesis and takes the title "Moral Development Method in Increasing Worship Practice Students in Middle School 4 in East Lampung Sekampung" The purpose of this study was to determine the level of moral deviation of students, to know the method of religious education teachers Islam, both in terms of supporting and inhibiting factors in the moral development of students and how much the practice of worship of the students increases. The research that the author is doing is included in descriptive qualitative research, and in the course of collecting data, the author uses observation, documentation, and interview methods. While for the analysis, the author uses qualitative descriptive analysis techniques, namely: in the form of written or oral data from people and behavior that is observed so that in this case the author seeks to conduct research that is describing thoroughly about the actual situation.The results of the research conducted by the author can be conveyed here, that the coaching method that the author offers in the discussion of this thesis is one way that can be done to find the best solution to the problem of moral development methods used by PAI teachers in increasing the practice of worship of students. And the efforts made by the teachers of Islamic religious education are one of the ways to foster the morale of those who have been deceived. Even if there are still other alternatives that might be better than what have been submitted or written in this thesis, then this can be used as input or additional so that this thesis continues to grow and does not stop here